Correlation between culture testing of swabs and ligase chain reaction of first void urine from patients recently treated for Chlamydia trachomatis. Issue 3 (1st June 2003) - Jang, D; Sellors, J; Howard, M; Mahony, J; Frost, E; Patrick, D; Bouchard, C; Dubois, J; Scholar, L; Chernesky, M
Abstract : We assessed the correlation between ligase chain reaction (LCR) on first void urine (FVU) and cultures of urethral and cervical swabs to detect chlamydia during three post-treatment follow up visits for 10 men and 19 women with genital chlamydial infections who had been treated with azithromycin or doxcycline.